(untitled) (Journal of Computational Mathematics, 2021)
In this paper, the linear finite element approximation to the elastic contact problem with curved contact boundary is considered. The error bound O(h^1/2) is obtained with requirements of two times continuously differentiable for contact boundary and the usual regular triangulation, while I.Hlavacek et. al. obtained the error bound O(h^3/4) with requirements of three times continuously differentiable for contact boundary and extra regularities of triangulation (c.f. [2]).